2003
DOI: 10.1074/jbc.m212856200
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Human Homologues of p47 and p67 Participate in Activation of Superoxide-producing NADPH Oxidases

Abstract: The catalytic core of a superoxide-producing NADPH oxidase (Nox) in phagocytes is gp91 phox /Nox2, a membrane-integrated protein that forms a heterodimer with p22 phox to constitute flavocytochrome b 558 . The cytochrome becomes activated by interacting with the adaptor proteins p47 phox and p67 phox as well as the small GTPase Rac. Here we describe the cloning of human cDNAs for novel proteins homologous to p47 phox and p67 phox , designated p41 nox and p51 nox , respectively; the former is encoded by NOXO1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
316
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(340 citation statements)
references
References 57 publications
(90 reference statements)
22
316
2
Order By: Relevance
“…Recent evidence suggests that Rac1 also regulates Nox1 most likely through GTP-dependent interactions with the Nox activator, Noxa1 [16][17][18][19] We showed that the association of Noxa1 with the plasma membrane depends on its interaction with Noxo1 [17]. These structural and functional similarities between the Nox and phox regulators may explain why Noxo1 and Noxa1 can function in partially compensating for p47 phox and p67 phox in supporting Nox2 activity [8,[13][14][15]. Noxo1, Noxa1, and Rac1 also support Nox3 activity, which appears to function critically in the inner ear [17,[20][21][22]; mice with lesions in either the NOX3 or NOXO1 gene have defects in sensing gravity resulting from impaired otoconia formation [23,24].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Recent evidence suggests that Rac1 also regulates Nox1 most likely through GTP-dependent interactions with the Nox activator, Noxa1 [16][17][18][19] We showed that the association of Noxa1 with the plasma membrane depends on its interaction with Noxo1 [17]. These structural and functional similarities between the Nox and phox regulators may explain why Noxo1 and Noxa1 can function in partially compensating for p47 phox and p67 phox in supporting Nox2 activity [8,[13][14][15]. Noxo1, Noxa1, and Rac1 also support Nox3 activity, which appears to function critically in the inner ear [17,[20][21][22]; mice with lesions in either the NOX3 or NOXO1 gene have defects in sensing gravity resulting from impaired otoconia formation [23,24].…”
Section: Introductionmentioning
confidence: 62%
“…Based on recent observations in Nox1 knockout mice, Nox1 is also thought to act in the cardiovascular system in the pressor response to Angiotensin II [11,12]. Nox1 expressed alone produces little superoxide, although its activity is significantly enhanced in the presence of two co-factors, Noxo1 and Noxa1, detected in colon epithelium that are homologous to p47 phox and p67 phox , respectively [13][14][15]. Noxo1 was proposed to act as a "Nox organizer" based on structural and functional similarities with p47 phox , which is a multi-modular "adaptor" protein that bridges interactions between the membrane (flavocytochrome b 558 and lipid) and p67 phox .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nox1 can function even in the absence of p22 phox , although p22 phox is required for the full activity of Nox1 [36]. Furthermore, Nox1 but not Nox2 can also be activated by the p47 phox homologue Noxo1 (Nox organizer 1) and the p67 phox homologue Noxa1 (Nox activator 1) [37].…”
mentioning
confidence: 99%
“…The proteins NOXO1 (Nox organizer 1) and NOXA1 (Nox activator 1) are novel homologs of p47phox and p67phox, respectively, that regulate the activity of Nox1 and Nox3 [7,24,44,151]. NOXO1 contains tandem SH3 domains that interact with p22phox like p47phox, but has no autoinhibitory domain like p47phox.…”
Section: Regulation Of Nadph Oxidasementioning
confidence: 99%